Slownik handlowy angielsko-polski - Woytowicz-Neymann, Monika; Kozierkiewicz, Roman; Pulawski, Mieczyslaw (Warszawa : Panstwowe Wydawn. Ekonomiczne, 1991)
A dictionary for the fields of economics and business as well as general phrases for conducting business; English/Polish.
Title on added t.p.: English-Polish business dictionary.
Includes bibliographical references.
Keywords: Commerce -- Dictionaries -- Polish; English language -- Dictionaries -- Polish